Age-related reference intervals for ambulatory electrocardiographic parameters in healthy individuals - Hashimoto, Kenichi; Harada, Naomi; Kimata, Motohiro; Kawamura, Yusuke; Fujita, Naoya; Sekizawa, Akinori; Ono, Yosuke; Obuchi, Yasuhiro; Takayama, Tadateru; Kasamaki, Yuji; Tanaka, Yuji (Frontiers in Cardiovascular Medicine, 2023)
Background: The advent of novel monitoring technologies has dramatically increased the use of ambulatory electrocardiography (AECG) devices. However, few studies have conducted detailed large-scale investigations on the incidence of arrhythmias over 24 h, especially ectopy, in healthy individuals over a wide age range. Objectives: This study aimed to investigate the incidence of arrhythmias detected using AECG and associated factors, in healthy individuals, over a wide age range. Methods: In this cross-sectional study, we performed AECG on 365 healthy volunteers (median [interquartile range]: 48 [36, 67], 20–89 years, 165 men) under free-running conditions for 24 h. Ultrasonic echocardiography and heart rate variability analysis were performed to explore the factors associated with the incidence of arrhythmias. Results: The 97.5th percentile of single ventricular ectopy (VE) was 149/day, 254/day, and 1682/day in the 20–39-, 40–59- and 60–89-year age groups, respectively; that of single supraventricular ectopy (SVE) was 131/day, 232/day, and 1063/day, respectively. Multivariate analysis revealed that aging was the only independent significant factor influencing the frequency of VE (β=0.207, P=0.001). Age (β=0.642, P<0.001), body mass index (BMI) (β=-0.112, P=0.009), and the root mean square of successive differences in RR intervals (β=0.097, P=0.035) were factors significantly associated with SVE frequency. Conclusions: Age-specific reference intervals of VE and SVE in a large population of healthy participants over a wide age range were generated. VE and SVE increased with age; SVE was influenced by BMI and the aging-induced decrease in parasympathetic tone activity.